Performance Improvement of the Yellow Zone in Emergency Department using Discrete Event Simulation Approach - Munira Ibrahim, Ireen; Liong, Choong-Yeun; Abu Bakar, Sakhinah; Farid Najmudd, Ahmad (International Journal of Engineering and Technology, 2018)
Overcrowding is a major concern for the Emergency Department (ED) management at the public hospital under study. Although the number of patients in the Yellow Zone (YZ) of the department represents only 30% of the total visiting patient per day, the Key Performance Indicator (KPI) of the zone’s patients’ LOS (LOS) as well as waiting time are not achievable due to the resources constraints. Therefore, this paper discusses the application of Discrete Event Simulation (DES) approach on modeling the YZ’s daily operations. The model was developed using Arena software to assist the ED management to better understand their system behavior and causes for the high patients’ LOS and waiting time. The simulation outputs show that the bottleneck of the system is waiting for an available resource. A few scenarios were designed based on the discussion made with the ED management for possible improvement. The results show a significant reduction of 25% and 35% in the total average of patients’ LOS for the patients of the observation unit and the intensive unit respectively. Meanwhile, for the total average patients’ waiting time, the results show a reduction of 34% for the observation unit and 29% reduction for the intensive unit.